Antibacterial activity of isopropoxy benzene guanidine against Riemerella anatipestifer - Lu, Yixing; Qiao, Weimei; Xue, Yaqian; Hong, Xiaoxin; Jin, Yuhang; Li, Jie; Peng, Xianfeng; Zeng, Dongping; Zeng, Zhenling (Frontiers in Pharmacology, 2024)
Riemerella anatipestifer (R. anatipestifer) is an important pathogen in waterfowl, leading to substantial economic losses. In recent years, there has been a notable escalation in the drug resistance rate of R. anatipestifer. Consequently, there is an imperative need to expedite the development of novel antibacterial medications to effectively manage the infection caused by R.anatipestifer. This study investigated the in vitro and in vivo antibacterial activities of a novel substituted benzene guanidine analog, namely, isopropoxy benzene guanidine (IBG), against R.anatipestifer by using the microdilution method, time-killing curve, and a pericarditis model. The possible mechanisms of these activities were explored. The minimal inhibitory concentration (MIC) range of IBG for R. anatipestifer was 0.5-2 μg/mL. Time-killing curves showed a concentration-dependent antibacterial effect. IBG alone or in combination with gentamicin significantly reduced the bacterial load of R. anatipestifer in the pericarditis model. Serial-passage mutagenicity assays showed a low probability for developing IBG resistance. Mechanistic studies suggested that IBG induced membrane damage by binding to phosphatidylglycerol and cardiolipin, leading to an imbalance in membrane potential and the transmembrane proton gradient, as well as the decreased of intracellular adenosine triphosphate. In summary, IBG is a potential antibacterial for controlling R. anatipestifer infections.